Justice palaces of bogotá. public building and tragic fate (2007)
In this article the justice palaces of Bogotá are analizedfrom their perspective of public buildings. The representativeduties are observed from the relation betweenarchitecture and institutions and the significance thatsociety has constructed around them. In accordance tothe symbolic meaning that these buildings acquire, asstate symbols of power, this study takes into account thesearch for an ideal representation and the performancethat is carried out in a specific context.